Microstructure Investigations of Natural Clay From Pattallassang District, Takalar Regency, South Sulawesi Province, Indonesia - Abd Rahman; Suriati Eka Putri; Diana Eka Pratiwi; Satria Putra Jaya (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2023)
The study aimed to investigate the microstructure of natural clay from Pattallassang District, Takalar Regency, South Sulawesi Province. The clay was characterized using X-ray diffractometer (XRD), surface area analyzer (SAA), and scanning electron microscope (SEM). The XRD analysis showed that the main mineral composition of the clay was kaolinite, quartz, hematite, geothite, magnetite, and anatase phases. The SAA using BET analysis shows the large surface area of 59.26 m2/g and BJH analysis for pore distribution of 32.77 nm. SEM observations revealed that the clay consists of plate-like kaolinite particles arranged randomly. The results indicate that the natural clay from Pattallassang District has good potential for use in various industrial applications due to its high kaolinite content and favorable microstructure.Keywords: kaolinite, microstructure, mineral, clay.